Cropping systems for Vertisols of the Ethiopian highlands - Tedla, A.; Mohamed-Saleem, M.A. (IBSRAM, 1992)
Discusses the traditional and potential cropping systems for the highlands of Ethiopia. Traditional Vertisol management methods of these soils fail to overcome waterlogging problems, and therefore croping practices vary from place to place to suit the length of time left after the water is naturally drained off. Hence to improve surface drainage, the use of broadbed maker introduced the possibilities of increasing the production of food and feed crops in various combinations and intensities as sole-and intercrops. Early planting, sequential cropping, and undersowing of cereals w. forage covers proved promising on drained Vertisols.